Consumerism, obesity, youth and civic development in Malaysia - Rodriguez, Adriana Maria Ortega; Ismail, Ismi Arif; Abdullah, Haslinda; Krauss, Steven Eric (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
The price of not addressing effectively the issues related to consumerism and ‘modern’ lifestyles have resulted very costly to society’s sustainable development, health and wellbeing. This might have, indirectly, detrimental impact on nations’ civic development, prosperity and human happiness. Thus, the importance of considering the effect that consumerism has on community’s health and wellbeing. For example, the rapid economic growth and marked socio-economic advancement in developing countries has resulted in significant changes in the lifestyles and consumer’s habits. An imminent and worrisome problem related to these changes is the increased prevalence of obesity among children and teenagers.